2016
DOI: 10.1080/07373937.2016.1230628
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional computational fluid dynamics (CFD) study of the gas–particle circulation pattern within a fluidized bed granulator: By full factorial design of fluidization velocity and particle size

Abstract: The fluidization velocity and mean particle size were selected to be numerically investigated pertaining to their effects on the gas-particle circulation pattern within a fluidized bed granulator by three-dimensional CFD simulation applying an Eulerian-Eulerian two-fluid model (EETFM). The CFD simulations were designed by full-factorial design method and the developed CFD model was experimentally validated.The fluidization process was proved to reach a quasi-steady state. The gas-particle circulation pattern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The bubbles began to form at the surface of the air distributor and were enlarged as they moved upwards due to the surface tension gradient. Similar hydrodynamic behaviour has been reported previously [10,13]. However, as depicted in Figure 10b, the formation and development of bubbles as described by the RNG k-ε turbulent model seems to be non-uniform when compared to that described by the laminar model.…”
Section: Development Of the Fluidisation Hydrodynamics Turbulent Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…The bubbles began to form at the surface of the air distributor and were enlarged as they moved upwards due to the surface tension gradient. Similar hydrodynamic behaviour has been reported previously [10,13]. However, as depicted in Figure 10b, the formation and development of bubbles as described by the RNG k-ε turbulent model seems to be non-uniform when compared to that described by the laminar model.…”
Section: Development Of the Fluidisation Hydrodynamics Turbulent Modelsupporting
confidence: 85%
“…Reliable models can facilitate the investigation of thermochemical processes associated with biomass gasification; likewise, they help to study and evaluate the effects of the operational parameters on the gasifier performance and product quality [6]. Numerical models and simulation studies for biomass gasification using either Eulerian [7][8][9][10][11] or Lagrangian (discrete element) [12][13][14] models have been the focus of many researchers in recent years. A large number of numerical modelling and simulation studies have been reported in literature on the complex behaviour of gas-solid mixing, as well as on the fluidization hydrodynamics, in order to formulate the problems and to devise solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pharmaceutical manufacturing industry, this technique is popularly adopted in many other industries including foods, detergent and fertilizers. Traditionally, batch granulation techniques have been employed in production of pharmaceutical granules (Crooks and Schade, 1978; Hemati, Cherif et al, 2003; Liu, Wang et al, 2013; Liu and Li, 2014; Liu and Li, 2014; Liu, Yoon et al, 2016). Recently, as the continuous manufacturing concept is introduced and discussed, implementation of a switch from batch granulation to continuous granulation has received attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this model can be used to navigate the design space. The residual versus predicted value and normal probability plots are two significant graphical approaches to check the validity of the regression model [43,49]. The results of the residual versus predicted value indicate the difference between predicted and observed values.…”
Section: Resultsmentioning
confidence: 99%
“…Design of experiments (DOE) is a systematic method to determine the relationship between factors affecting a process and to find the cause-and-effect relationship [42,43]. Design of Expert ® version 10 has been used for design of experiment and data analysis.…”
Section: Methodsmentioning
confidence: 99%